Effects of zwitterionic surfactant adsorption on the component distribution in the crude oil droplet: A molecular simulation study. (1st January 2021) - Lian, Peng; Jia, Han; Wei, Xin; Han, Yugui; Wang, Qiuxia; Dai, Jiajun; Wang, Daofan; Wang, Shaoyan; Tian, Zihao; Yan, Hui
Graphical abstract: Highlights: Dynamic behaviors of crude oil components and DDPS molecules are elaborated by MD simulation. Component polarity and interaction with water dominate their distribution in oil droplet. DDPS fabricate the well-organized adsorption layer to replace the original oil/water interface. The complex interaction between DDPS and components causes the redistribution of all components. Abstract: The intermolecular interaction between various components in crude oil, such as saturates, aromatics, resins, and asphaltenes, and the zwitterionic surfactant 3-(decyldimethylazaniumyl) propane-1-sulfonate (DDPS) are investigated in detail via molecular dynamics (MD) simulation and quantum chemistry calculations. The radial distribution function (RDF) is calculated to reflect the effects of the charged functional group, aromatic ring, and heteroatom on the component distribution and configuration in the crude oil droplet. The additional DDPS molecules could fabricate the well-organized adsorption layer at the crude oil surface to replace the original oil/water interface, leading to the obvious movement of the components in both hydrophobic interior and interfacial layer of crude oil droplet. Furthermore, the reduced density gradient (RDG) method is employed to visualize the intermolecular interaction. It is demonstrated that the complex interaction (hydrophobic, electrostatic, and cation-π interaction) between DDPS molecules and related components should be responsible for the final distribution and configuration of various components in the crude oil/water/DDPS system.